Design of flexible inorganic BiFe0.93Mn0.07O3 ferroelectric thin films for nonvolatile memory - Bingbing Yang; Chenhui Li; Miao Liu; Renhuai Wei; Xianwu Tang; Ling Hu; Wenhai Song; Xuebin Zhu; Yuping Sun (Journal of Materiomics, 2020)
Flexible ferroelectric memories, endowing with high data storage density, provide a chance for the next-generation wearable electronics. Here, flexible inorganic Mn-doped BiFeO3 thin films were directly integrated on fluorophlogopite mica (F-Mica) substrates by an easy and low-cost all solution chemical solution deposition (AS-CSD) route. The integration of LaNiO3 buffer layer can improve the film surface density and uniformity. The flexible characteristic can be achieved by reducing the thickness of F-Mica substrates for the ferroelectric thin films. In contrast to BiFe0·93Mn0·07O3/LaNiO3/Si thin film deposited on rigid substrates (Si), the BiFe0·93Mn0·07O3/LaNiO3/F-mica fabricated on F-Mica show better ferroelectric performances due to the improved crystal growth and less defects. More importantly, the obtained BiFe0·93Mn0·07O3/LaNiO3/F-mica ferroelectric thin films still show large remnant polarization of Pr ∼64 μC/cm2 (deterioration of ∼7.2%), good antifatigue properties up to 1.2 × 108 cycles and outstanding retention behaviors for 1.6 × 104 s after continuous bending. This work will provide a feasible route to fabricate flexible inorganic ferroelectric thin films through low-cost solution method and show attractive comprehensive performances in next-generation wearable smart devices.